2022
DOI: 10.1039/d2gc01211a
|View full text |Cite
|
Sign up to set email alerts
|

Formic acid–hydrogen peroxide treatment of furfural residue for production of nanocellulose, lignin, and nano-scale lignin

Abstract: Further utilization of furfural residue, an industrial solid waste, has been a long-termed challenge because of its hostile properties toward the applications, such as strong acidity and high salinity. Herein,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In the aromatic regions, the C 2,6 –H 2,6 correlation of the S units was distinguished at δ C /δ H 103.8/6.68 ppm; a minor but clear signal at δ C /δ H 110.9/7.01 was related to the C 2 –H 2 correlation of the G units. In addition, a correlated signal of the C 2,6 –H 2,6 correlation from the H units could be detected at δ C /δ H 128.0/7.10 [ 27 ]. The linkage-bond content was obtained by the quantitative calculation of the β-O-4 linkage bond in IL and DIL.…”
Section: Resultsmentioning
confidence: 99%
“…In the aromatic regions, the C 2,6 –H 2,6 correlation of the S units was distinguished at δ C /δ H 103.8/6.68 ppm; a minor but clear signal at δ C /δ H 110.9/7.01 was related to the C 2 –H 2 correlation of the G units. In addition, a correlated signal of the C 2,6 –H 2,6 correlation from the H units could be detected at δ C /δ H 128.0/7.10 [ 27 ]. The linkage-bond content was obtained by the quantitative calculation of the β-O-4 linkage bond in IL and DIL.…”
Section: Resultsmentioning
confidence: 99%
“…19,20 HP together with formic acid and citric acid has also been shown to form a powerful peroxyacid system and has made great contributions to delignification. 21,22 Owing to its monocarboxylic acid structure and acidic properties, GA along with HP (HP-GA) seems to be a promising alternative in lignin removal. Moreover, unlike several extensively reported peroxyacids, the use of HP-GA has not been reported.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Organic peracid pretreatment is considered to be an effective method for the selective removal of lignin while preserving the carbohydrates in biomass . It has been repeatedly reported that peroxyacetic acid formed from hydrogen peroxide (HP) and acetic acid could be used for the delignification of lignocellulosic biomass to significantly improve the enzymatic digestibility of cellulose. , HP together with formic acid and citric acid has also been shown to form a powerful peroxyacid system and has made great contributions to delignification. , Owing to its monocarboxylic acid structure and acidic properties, GA along with HP (HP-GA) seems to be a promising alternative in lignin removal. Moreover, unlike several extensively reported peroxyacids, the use of HP-GA has not been reported.…”
Section: Introductionmentioning
confidence: 99%